Carbon nanotubes modified with ZnO nanoparticles: High-efficiency electromagnetic wave absorption at high-temperatures. Issue 3 (April 2015) - Kong, Luo; Yin, Xiaowei; Han, Meikang; Zhang, Litong; Cheng, Laifei
Abstract: Carbon nanotube–ZnO composite powders, which act as high-temperature electromagnetic wave absorbents, are prepared by homogeneous precipitation. Carbon nanotube–ZnO/glass composites are fabricated by pressureless sintering. ZnO nanoparticles are assembled on the surface of carbon nanotubes, which produces heterostructure and enhances polarization at heterogeneous interface. Owing to the consumption of an amorphous carbon layer on the outer surface of carbon nanotubes and the generation of oxygen vacancies in ZnO during sintering, a higher concentration of charge carriers is produced in ZnO, which causes more relaxation polarization and dielectric loss in electromagnetic field. Owing to the shortened relaxation time, and the increase of relaxation polarization, permittivity and dielectric loss increases with the increase in testing temperature. Reflection coefficient of the obtained composite reaches −70 dB. The special integration of multiwalled carbon nanotubes modified with some metal oxide semiconductor nanoparticles provides an effective approach to design high-temperature electromagnetic absorbing materials.